Efficacy and Safety of Subcutaneous Belimumab in Anti–Double‐Stranded DNA–Positive, Hypocomplementemic Patients With Systemic Lupus Erythematosus. Issue 8 (15th June 2018) - Doria, A.; Stohl, W.; Schwarting, A.; Okada, M.; Scheinberg, M.; van Vollenhoven, R.; Hammer, A. E.; Groark, J.; Bass, D.; Fox, N. L.; Roth, D.; Gordon, D.
Abstract : Objective: To investigate the efficacy and safety of belimumab, a human immunoglobulin monoclonal antibody against B lymphocyte stimulator, in a subset of patients with systemic lupus erythematosus (SLE) who were hypocomplementemic (C3 <90 mg/dl and/or C4 <10 mg/dl) and anti–double‐stranded DNA (anti‐dsDNA) positive (≥30 IU/ml) at baseline. Methods: In this phase III, double‐blind, placebo‐controlled study (BEL112341; ClinicalTrials.gov identifier: NCT01484496), patients with moderate to severe SLE (Safety of Estrogens in Lupus Erythematosus National Assessment version of the Systemic Lupus Erythematosus Disease Activity Index [SELENA–SLEDAI] score ≥8) were randomized (2:1) to receive weekly subcutaneous (SC) belimumab 200 mg or placebo, plus standard SLE therapy, for 52 weeks. The primary end point was SLE Responder Index 4 (SRI‐4) response rate at week 52. Secondary end points were time to severe flare and reduction in corticosteroid dose (weeks 40–52). Safety was assessed throughout. Results: Of the 836 patients in the intent‐to‐treat (ITT) population, 356 were hypocomplementemic and anti‐dsDNA positive at baseline (108 in the placebo group and 248 in the SC belimumab 200 mg group). Compared with placebo, the belimumab group contained more SRI‐4 responders (47.2% versus 64.6%; P = 0.0014),  had a lower incidence of severe flare according to the SELENA‐SLEDAI flare index (31.5% versus 14.1%),  and had a greater percentage of patients who reduced corticosteroid dosage by ≥25% to ≤7.5 mg/day during weeks 40–52 (11.4% versus 20.7%; P = 0.0844). Adverse events (AEs) were similar between treatment groups. Conclusion: Our findings indicate that in hypocomplementemic, anti‐dsDNA–positive SLE patients, weekly SC belimumab 200 mg significantly improves SRI‐4 response, decreases severe flare incidence, and reduces corticosteroid use versus placebo; a trend toward greater benefit compared with the overall ITT population was observed. AEs were consistent with the known safety profile of belimumab.